Abnormal beta power is a hallmark of explicit movement control in functional movement disorders. (16th January 2018) - Teodoro, Tiago; Meppelink, Anne Marthe; Little, Simon; Grant, Robert; Nielsen, Glenn; Macerollo, Antonella; Pareés, Isabel; Edwards, Mark J.
Abstract : Objective: To determine whether sensorimotor beta-frequency oscillatory power is raised during motor preparation in patients with functional movement disorders (FMD) and could therefore be a marker of abnormal "body-focused" attention. Methods: We analyzed motor performance and beta-frequency cortical oscillations during a precued choice reaction time (RT) task with varying cue validity (50% or 95% congruence between preparation and go cues). We compared 21 patients with FMD with 13 healthy controls (HCs). Results: In HCs, highly predictive cues were associated with faster RT and beta desynchronization in the contralateral hemisphere (contralateral slope −0.045 [95% confidence interval (CI) −0.057 to −0.033] vs ipsilateral −0.033 [95% CI −0.046 to −0.021], p < 0.001) and with a tendency for reaching lower contralateral end-of-preparation beta power (contralateral −0.482 [95% CI −0.827 to −0.137] vs ipsilateral −0.328 [95% CI −0.673 to 0.016], p = 0.069). In contrast, patients with FMD had no improvement in RTs with highly predictive cues and showed an impairment of beta desynchronization and lateralization before movement. Conclusions: Persistent beta synchronization during motor preparation could reflect abnormal explicit control of movement in FMD. Excessive attention to movement itself rather than the goal might maintain beta synchronization and impair performance.